A novel HSD17B10 mutation impairing the activities of the mitochondrial RNase P complex causes X-linked intractable epilepsy and neurodevelopmental regression. Issue 5 (3rd May 2016) - Falk, Marni J.; Gai, Xiaowu; Shigematsu, Megumi; Vilardo, Elisa; Takase, Ryuichi; McCormick, Elizabeth; Christian, Thomas; Place, Emily; Pierce, Eric A.; Consugar, Mark; Gamper, Howard B.; Rossmanith, Walter; et al.
ABSTRACT: We report a Caucasian boy with intractable epilepsy and global developmental delay. Whole-exome sequencing identified the likely genetic etiology as a novel p.K212E mutation in the X-linked gene HSD17B10 for mitochondrial short-chain dehydrogenase/reductase SDR5C1. Mutations in HSD17B10 cause the HSD10 disease, traditionally classified as a metabolic disorder due to the role of SDR5C1 in fatty and amino acid metabolism. However, SDR5C1 is also an essential subunit of human mitochondrial RNase P, the enzyme responsible for 5′-processing and methylation of purine-9 of mitochondrial tRNAs. Here we show that the p.K212E mutation impairs the SDR5C1-dependent mitochondrial RNase P activities, and suggest that the pathogenicity of p.K212E is due to a general mitochondrial dysfunction caused by reduction in SDR5C1-dependent maturation of mitochondrial tRNAs.